Building a trauma-responsive educational practice : lessons from a corrections classroom - Daniels, Em (New York, NY : Routledge, 2022)
"This timely manual presents a new perspective on teaching and learning focused on countering the impacts of trauma on adults' ability to learn. Within its detailed and useful approaches, Daniels provides a roadmap for building a Trauma-Responsive teaching practice grounded in the principles of Trauma-Informed Care, and emphasizing the need for educators to develop a rigorous practice of self-care. Prison classrooms, in particular, demonstrate the intersectional and overlapping nature of systemic, historical, and individual traumatic experience. People who rediscover themselves as learners while in corrections classrooms have a unique and powerful perspective to bring to the work of ending mass incarceration, and the role of education and learning in that ending. The concepts and framework presented in the text aim to expand how we define "working with trauma." Through this redefinition, we better align teaching and learning as counters to the impacts of trauma. As this alignment transforms educational philosophy and practice, we have an opportunity to repurpose the nature of education itself, and shift toward learning how to learn. Although this book contains content specific to corrections educators, or those aspiring to teach in prisons, its concepts and activities are applicable to any environment or situation in which adults need to learn. Adult educators, front-line personnel in any public service role, librarians, legal professionals, judges, lawyers - all can benefit from the expertise shared in this book"--
Keywords: Prisoners -- Education; Education -- Philosophy; Corrections; SOCIAL SCIENCE / Criminology